THE CHARACTERISTICS OF FORAMINIFERAL COMMUNITY IN JAKARTA BAY - Ricky Rositasari (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
Jakarta bay is a unique water since there are hydrological and ecological complexity. In general, the feature of these water consist of three ecological elements that are estuaries, coral reefs and open sea. Each of these ecological element has different hydrology, ecology as well as biological characteristics. As a form of meiobenthic community, foraminifera has adaptive behavior to each of ecological element of the waters. The observation on foraminiferal adaptive behavior due to the hydrological condition of Jakarta Bay was conducted from 2003 to 2009. The result showed that foraminiferal distribution was tend to pursue to the degradation water conditions and constructed a specific pattern. Coastal water and estuary were found dominated by Ammonia beccarii, Calcarine and other larger benthic foraminifera were common in coral reef area, Elphidium and Nonion depressulum were common in open waters area. Based on the diversity indices, the foraminifera in Jakarta Bay has a higher diversity compared to foraminifera in the coastal water of Semarang and Cirebon and among the ecological element of Jakarta Bay, reef area has the highest diversity index than coastal nor open sea area.Keywords: Foraminifera, Calcarine, Jakarta Bay